PERAN KOMPONEN 5A PADA KEPUASAN PENGUNJUNG (STUDY EMPIRIS DESTINASI WISATA TAMAN BUNGA CELOSIA) - Dwi Sekar Parawansah; Vira Melinda Tyawardani; Luluk Dian Ramadanti; Dela Amaliatus Solekah; Ratih Pratiwi (Sekolah Tinggi Ilmu Ekonomi AMA Salatiga, 2022)
This study aimed to determine the role of component 5A on visitor satisfaction Celosia flower garden. The population in the study are all visitors to the celosia flower garden in 2019-2021. The sampling technique used is simple random sampling of 100 people. From the research results show the results of the regression equation Y=19.483+7.181X, namely component 5A has a positive and significant impact on visitor satisfaction with a significant value of 0.000 <0.05, thus the hypothesis can be accepted.